Respiratory reference values for bottlenose dolphins ( Tursiops spp.) and its importance for conservation - Fabien Cauture; Jay Sweeney; Rae Stone; Andreas Fahlman (Marine Mammal Science, 2025)
Respiratory disease is one of the main causes for morbidity and mortality in cetaceans, which highlights the importance of understanding normal lung function and how it may impede homeostasis, and diving capacity. In addition, the use of breathing frequency as a proxy for metabolic rate requires a better estimate of the normal range of tidal volume, respiratory flow, and breath durations. In the current study, we use data on clinically healthy bottlenose dolphins ( Tursiops spp . ) collected over a decade to define how lung function varies with body mass, age, and sex while in water or during voluntary beaching. The data show that tidal volume consistently varies with body mass both during spontaneous and forced breaths both in water and while beached. Both peak expiratory and inspiratory flow varies with body mass, but also in some circumstances with sex and age. Total and inspiratory breath durations only varied with body mass during forced breaths on land. Expired tidal volume varied with both body mass and either total or expiratory breath duration. These data provide baseline for respiratory function in healthy bottlenose dolphins and suggest that either total or expiratory breath duration provide a useful proxy for tidal volume.

Deep diving by offshore bottlenose dolphins ( Tursiops spp.) - Andreas Fahlman; Reny B. Tyson Moore; Rae Stone; Jay Sweeney; Robyn Faulkner Trainor; Aaron A. Barleycorn; Katherine McHugh; Jason B. Allen; Randall S. Wells (Marine Mammal Science, 2023)
We used satellite‐linked tags to evaluate dive behavior in offshore bottlenose dolphins ( Tursiops spp.) near the island of Bermuda. The data provide evidence that bottlenose dolphins commonly perform both long (>272 s) and deep (>199 m) dives, with the deepest and longest dives being to 1,000 m and 826 s (13.8 min), respectively. The data show a relationship between dive duration and dive depth for dives longer than about 272 s. There was a diurnal pattern to dive behavior, with most dives deeper than 50 m being performed at night; deep diving began at sunset and varied throughout the night. We used the cumulative frequency of dive duration to estimate a behavioral aerobic dive limit (bADL) of around 560–666 s (9.3–11.1 min) in adult dolphins in this population. Dives exceeding the bADL spent significantly longer time in the upper‐most 50 m following a dive as compared with dives less than the bADL. We conclude that the offshore ecotype off Bermuda, unlike the shallow‐diving near‐shore bottlenose dolphin, is a deep‐diving ecotype, and may provide a useful animal model to study extreme diving behavior and adaptations.

Surface and diving metabolic rates, and dynamic aerobic dive limits ( dADL ) in near‐ and off‐shore bottlenose dolphins, Tursiops spp., indicate that deep diving is energetically cheap - Andreas Fahlman; Austin S. Allen; Ashley Blawas; Jay Sweeney; Rae Stone; Robyn Faulkner Trainor; Frants H. Jensen; Katherine McHugh; Jason B. Allen; Aaron A. Barleycorn; Randall S. Wells (Marine Mammal Science, 2023)
High‐resolution dive depth and acceleration recordings from nearshore (Sarasota Bay, dive depth Tursiops spp.) were used to estimate the diving metabolic rate (DMR) and the locomotor metabolic rate (LMR, L O 2 /min) during three phases of diving (descent, bottom, and ascent). For shallow dives (depth ≤ 30 m), we found no differences between the two ecotypes in the LMR during diving, nor during the postdive shallow interval between dives. For intermediate (30 m 100 m), the LMR was significantly higher during ascent than during descent and the bottom phase by 59% and 9%, respectively. In addition, the rate of change in depth during descent and ascent (meters/second) increased with maximal dive depth. The dynamic aerobic dive limit (dADL) was calculated from the estimated DMR and the estimated predive O 2 stores. For the Bermuda dolphins, the dADL decreased with dive depth, and was 18.7, 15.4, and 11.1 min for shallow, intermediate, and deep dives, respectively. These results provide a useful approach to understand the complex nature of physiological interactions between aerobic metabolism, energy use, and diving capacity.

An evaluation of freshwater bath treatments for the control of sea lice, Lepeophtheirus salmonis (Krøyer), infections in Atlantic salmon, Salmo salar L. - J Stone; S Boyd; C Sommerville; G H Rae (Journal of Fish Diseases, 2002)